Public policy process: The system of actions - Abdullahi, Aliyu (2020)
Public Policy is a formal documented statement of intentions and sets of actions of a government to either remove certain deficiencies or improve the conditions in any particular area of concern/interest. It is “whatever governments choose to door not to do” and it as a system of laws, regulatory measures, courses of actions and funding priorities concerning a given topic promulgated by a governmental entity its representatives. Public policy is very crucial to public sector managers because public policy is one subject that affects the lives and well being of the people and the knowledge of it will adequately equip the public sector managers with clearer understanding of the reasons for some, if not all of governments thought process and its actions or inaction's. This will help public sector managers to proffer intelligent advice to the government. From the literature, there are three reasons for studying public policy. They include; a) professional reasons, b) scientific reasons and c) political reasons. The analyses of the nature, basic elements and scopes as well as types of public policies in this unit have elucidated more on public policy analysis. The effort was geared to make you a good public policy analyst. There are still other types of public policy like reversible and irreversible policies, explicit and implicit policies, material and symbolic policies as well as collective good-private good policies.